Investigation of the conformation changes of myoglobin by an electrochemical method and a biosensing application based on controlled protein unfolding. Issue 12 (21st June 2015) - Liu, Jianbo; Zheng, Jianbin; Zhang, Juncai; Bai, Wushuang; Liu, Jiangtao
<x xml:space="preserve">Abstract</x> The conformational changes of myoglobin (Mb) during urea-induced unfolding were investigated using an electrochemical method.